CLOVES Syndrome: A Review of Clinical, Genetic, and Therapeutic Aspects - Julianna Podolec; Silvia Ciraolo; Joanna Wojda; Adam Sobiński; Zuzanna Kościuszko; Katarzyna Kurza; Agnieszka Kulczycka-Rowicka; Matylda Czerwonka; Katarzyna Lesiczka-Fedoryj; Anna Walczak (Quality in Sport)
Purpose of Research: The research aims to provide an in-depth understanding of CLOVES syndrome, detailing its clinical features, epidemiology, etiology, and diagnostic criteria. It focuses on the role of PIK3CA gene mutations, challenges in diagnosis, and treatment options, including PI3K/AKT/mTOR pathway inhibitors.